Two new synonyms and a species reinstated in Phoradendron Nuttall (Viscaceae) - Caires, Claudenir Simões (2007)
Three taxonomic changes are proposed based on intensive collecting of Viscaceae within the Distrito Federal, Brazil. Phoradendron andersonii Rizzini, previously a synonym of P. perrottetii (DC.) Eichler is reinstated based on the following combination of characters: young internodes compressed with sharp angles at the distal ends, short spikes to 2.5 cm long, articles with intermixed male and female flowers, biseriate flowers, and dirty yellow fruits. Phoradendron irwinianum Kuijt is synonymized under P. apiciflorum Rizzini, previously known only from the type from western Minas Gerais. Finding of the type collection of P. brachyklados Rizzini, incorrectly quoted in the protologue, led to the synonymization proposal of this species under P. hexastichum (DC.) Grisebach.